Strategi Kepala Sekolah Dalam Meningkatkan Kinerja Guru SMPN 6 Sawahlunto - Sri Rahmawati; Suswati Hendriani (Departement of Mathematics Education, 2024)
The principal as the manager of an educational institution has a very important strategy, because the principal builds teacher performance so that teachers are enthusiastic in carrying out their duties. This type of research uses descriptive qualitative research. Data collection was carried out by observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. To test the validity of the data using triangulation. The results of this research show that: the principal's strategy in improving teacher performance at SMPN 6 Sawahlunto is providing motivation, fostering discipline, providing good perceptions, physical, mental and moral development, showing exemplary attitudes and behavior that becomes a role model, and developing teacher performance.